Rab family of small GTPases: an updated view on their regulation and functions - Homma, Yuta; Hiragi, Shu; Fukuda, Mitsunori (The FEBS journal, 2021)
The Rab family of small GTPases regulates intracellular membrane trafficking by orchestrating the biogenesis, transport, tethering, and fusion of membrane‐bound organelles and vesicles. Like other small GTPases, Rabs cycle between two states, an active (GTP‐loaded) state and an inactive (GDP‐loaded) state, and their cycling is catalyzed by guanine nucleotide exchange factors (GEFs) and GTPase‐activating proteins (GAPs). Because an active form of each Rab localizes on a specific organelle (or vesicle) and recruits various effector proteins to facilitate each step of membrane trafficking, knowing when and where Rabs are activated and what effectors Rabs recruit is crucial to understand their functions. Since the discovery of Rabs, they have been regarded as one of the central hubs for membrane trafficking, and numerous biochemical and genetic studies have revealed the mechanisms of Rab functions in recent years. The results of these studies have included the identification and characterization of novel GEFs, GAPs, and effectors, as well as post‐translational modifications, for example, phosphorylation, of Rabs. Rab functions beyond the simple effector‐recruiting model are also emerging. Furthermore, the recently developed CRISPR/Cas technology has enabled acceleration of knockout analyses in both animals and cultured cells and revealed previously unknown physiological roles of many Rabs. In this review article, we provide the most up‐to‐date and comprehensive lists of GEFs, GAPs, effectors, and knockout phenotypes of mammalian Rabs and discuss recent findings in regard to their regulation and functions. The Rab family of small GTPases regulates intracellular membrane trafficking by localizing on specific organelles (or vesicles) and recruiting various effector proteins to facilitate each step of membrane trafficking. In this review article, we provide the most up‐to‐date and comprehensive lists of guanine nucleotide exchange factors, GTPase‐activating proteins, effectors, and knockout phenotypes of mammalian Rabs and discuss recent findings in regard to their regulation and functions.